The Influence Of Marketing Strategies On Consumer Satisfaction At Salsabila Souvenir Shops In Padang City - Rosyadah, Nyiayu Amrina; Angraini, Ezi (Universitas Negeri Padang, 2023)
This study aims to examine and analyze the effect of product quality, price, location, promotion, distribution on consumer satisfaction of Salsabila Souvenir Shop in Padang City and examine and analyze the effect of product quality, price, location, promotion, and distribution simultaneously affect consumer satisfaction of Salsabila Souvenir Shop in Padang City. The type of research used is descriptive and causal research. The population in this study is all consumers of Salsabila Souvenir Shop in Padang City with a sample of 96 people. Data collection techniques are carried out by distributing questionnaires (questionnaires). The data were analyzed using multiple regression analysis. The result of this study is the presence of a negative but significant influence between product variables (X1) to variable Y (Consumer Satisfaction). There is a positive and significant influence between the price variable (X2) and the variable Y (Consumer Satisfaction). There is a positive and significant influence between the location variable (X3) and variable Y (Consumer Satisfaction). There is a positive and significant influence between the promotion variable (X4) and variable Y (Consumer Satisfaction). There is a negative and insignificant influence between the distribution variable (X5) and variable Y (Consumer Satisfaction). Product variables (X1), price (X2), location (X3), promotion (X4), and distribution (X5) simultaneously affect variable Y (Consumer Satisfaction) by 83.1% overall.